Biological Control of Spider Mites (Tetranychus Urticae Koch) in Tomato Crops - Dalabaevna, Muminova Rano (American Journal of Biology and Natural Sciences, 2026)
The two-spotted spider mite, Tetranychus urticae Koch, represents a significant threat to global tomato (Solanum lycopersicum) production, causing extensive leaf damage and yield loss through sap-sucking activity. Due to the rapid evolution of acaricide resistance in mite populations and growing environmental concerns, biological control has emerged as a critical component of Integrated Pest Management (IPM) for this pest. This article reviews the primary biological strategies used to suppress T. urticae in tomato crops. Key focus is placed on the use of predatory mites from the Phytoseiidae family, particularly Phytoseiulus persimilis and Neoseiulus californicus, highlighting their efficacy and the challenges posed by tomato glandular trichomes. Furthermore, the role of entomopathogenic fungi, such as Beauveria bassiana, and the application of botanical extracts are discussed as complementary tools. The integration of host plant resistance, derived from wild tomato relatives, is also examined as a sustainable long-term solution. Synthesis of current research suggests that a multi-trophic approach combining predatory release with microbial biopesticides can achieve high suppression levels while reducing chemical inputs. This review provides a foundation for developing effective, eco-friendly management protocols for spider mite control in both greenhouse and open-field tomato cultivation.